Multiple mechanisms regulate c-myc gene expression during normal T cell activation. - Lindsten, T (1988)
Quiescent normal human T cells express low levels of steady-state c-myc mRNA as a result of low constitutive promoter utilization, a block to transcriptional elongation within the gene, and rapid degradation of c-myc mRNA in the cytoplasm. Following the activation of the T cell receptor (TCR)/CD3 complex, quiescent T cells are induced to express c-myc mRNA. Two intracellular pathways, one involving protein kinase C activation and the other mediated by increased intracellular calcium concentration, are activated by TCR/CD3 receptor stimulation. These two pathways, which can be activated by phorbol myristate acetate (PMA) and ionomycin respectively, appear to play complementary roles in the transcriptional induction of c-myc gene expression by the antigen receptor complex. Ionomycin treatment of quiescent cells leads to enhanced c-myc expression primarily as a result of increased transcriptional initiation. In contrast, PMA contributes to c-myc expression, at least in part, by decreasing the block to transcriptional elongation present within the gene. Both the PMA- and ionomycin-mediated induction of c-myc expression can be independently enhanced by stabilization of c-myc mRNA in the cytoplasm. These observations demonstrate that multiple mechanisms co-operate to regulate c-myc gene expression during normal T cell activation.